Hope, Dickinson County - Kohman, Craig (Kansas State University, The Chapman Center for Rural Studies, 2012)
Author recreates the town of Hope using historic plat maps that he used to draw the actual extent of the town.
Craig Kohman, “Hope, Dickinson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/73.
Keywords: Abilene; Council Grove; Dwight D. Eisenhower; Dickinson County; Missouri Pacific Railroad; Joe Niemeier